Incorporating higher learning skills into bioethics education of multicultural students of science in Malaysia - Mohd Nor, S.N.; Mohamed, M.S.; Sivaraman, M.A.F.; Yan, S.H. (2014)
An overview of bioethics courses offered to pure science undergraduates from the University of Malaya is presented. Students come from three ethnic groups affiliated with three major religions with diverse values and belief systems. It was therefore important to incorporate a bioethics curriculum where the youths could identify with and relate to their intrinsic beliefs and moral discernment. For example, the concept of non-violence is an important ethical rule for the Hindus and Buddhists affecting their stand related to embryonic stem cell research. Likewise the concept of charity in Islam and Christianity would be important virtues to consider in regards to organ transplant issues. Two overriding concerns when designing the bioethics curriculum are therefore discussed in this paper: (1) the rationale for a course structure that accommodates varying ethical values on issues of scientific research and innovation, and (2) a suitable course design should incorporate and induce critical thinking and problem-solving skills. Positive feedback was received from students through a course evaluation survey and most students reported having fun while tackling ethical problems collectively in a peer group.